2006
DOI: 10.1159/000090681
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Biologically-Inspired Directional Microphone for Hearing Aids

Abstract: The development of novel microfabrication techniques for producing a directional microphone for hearing aids is here described. The mechanisms underlying both the structure and function of these unusual microphones were originally inspired by the ears of an inconspicuous insect, the parasitoid fly Ormia ochracea. The structure of Ormia’s ears inspired new approaches to design directional microphones that are more sensitive and have lower thermal noise than that typical of those using traditional approaches. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…The microphone diaphragms again had dimensions of 1 ϫ 2 mm 2 and were fabricated out of polycrystalline silicon. These diaphragms have also been described in Miles et al ͑2004͒ andHoy ͑2006͒ and are predecessors of the design described in the present study. Saito et al ͑2002͒ reported a microphone diaphragm inspired by Ormia's ears that is supported on a gimbal.…”
Section: Other Studies Of Ormia-inspired Microphonessupporting
confidence: 53%
“…The microphone diaphragms again had dimensions of 1 ϫ 2 mm 2 and were fabricated out of polycrystalline silicon. These diaphragms have also been described in Miles et al ͑2004͒ andHoy ͑2006͒ and are predecessors of the design described in the present study. Saito et al ͑2002͒ reported a microphone diaphragm inspired by Ormia's ears that is supported on a gimbal.…”
Section: Other Studies Of Ormia-inspired Microphonessupporting
confidence: 53%
“…12 The proportion of the two modes in the response could be used to determine the intensity difference response of the coupled circuit. We assume…”
Section: Parametric Studymentioning
confidence: 99%
“…sound) in a limited time frame [1]. Designing acoustic sensors such as MEMS microphones, which are inspired by nature is not new [2][3][4]. Moreover, a novel acoustic bio-inspired concept was recently presented in [5] where the "transducer becomes part of the signal processing chain".…”
Section: Introductionmentioning
confidence: 99%